UMP and PSDM sign joint agreement in book research and publication - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 10 April 2023 - Universiti Malaysia Pahang (UMP) and Perbadanan Stadium Darul Makmur (PSDM) signed a joint agreement on the research, writing, editing, printing and publication of the book ‘Memoir Lima Dekad: Perbadanan Stadium Darul Makmur, 1973-2023’ in conjunction with the Golden Jubilee Celebration of Stadium Darul Makmur this year.